High exposure mining occupations are associated with obstructive lung disease, National Health Interview Survey (NHIS), 2006‐2015. Issue 9 (12th July 2018) - Mabila, Sithembile L.; Almberg, Kirsten S.; Friedman, Lee; Cohen, Robert
Abstract : Background: The association between mining occupation categories and obstructive lung disease (OLD) has not been well explored in the United States. Methods: National Health Interview Survey (NHIS) data from 2006 to 2015 was used to determine the relationship between mining occupations and diagnosis of chronic bronchitis, emphysema, chronic obstructive pulmonary disease (COPD), and asthma. We classified occupations into low, moderate, high, and very high dust exposure groups. Extraction workers were categorized as very high dust exposure. Results: We found 4.5% of miners had chronic bronchitis, 3.3% had emphysema, 6.2% had COPD, and 9.9% had asthma. In fully adjusted models, extraction workers had significantly increased odds of having chronic bronchitis (OR = 2.18 [95%CI: 1.02, 4.64]), emphysema (OR = 7.85 [95%CI: 1.70, 36.27]), and COPD (OR = 2.56 [95%CI: 1.29, 5.12]) compared to lower exposure occupations. Conclusions: Occupation is an important predictor of OLD in the mining industry